Analisis Pendapatan Regional Kawasan Ekonomi Khusus Wilayah Papua Barat - Rully Wurarah; Sarce B. Awom (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
Special Economic Zones (SEZ) are one of the drivers of economic activity supported by various investment activities. The development of Sorong City SEZ is marked by the increasing interest of investors in developing their businesses, both in the industrial sector which has an impact on the formation of added value in the form of increased income and output of the GRDP, as well as in other economic sectors. The analysis of the data collected was done descriptively and tabulated to see changes in income over the past 5 years. The results obtained indicate that there has been an increase in income planning in each region (Sorong Regency, Raja Ampat Regency and Sorong City). Sorong City per capita income which is more dominant shows that the added value of the service sector is more competitive compared to other sectors. The development of Sosong City as a central KEK has encouraged the development of Sorong Regency and Raja Ampat Regency, so that it is important to note that the two regencies must be able to encourage the production factors which become inputs to the development of Sorong City. An important factor that must be considered in the development of the SEZ is the increase in population capacity as a factor of production and the development of home industries that utilize local raw materials to support the leading sectors in each region of the SEZ, so as to spur an increase in public income.